Bank specific and macroeconomics determinants of bank profitability in Malaysia / Amir Haniff Abdul Rahman - Abdul Rahman, Amir Haniff (2018)
Banks play a crucial role in the operation of most economies. The efficiency of financial intermediation can also affect economic growth. Besides that, bank insolvencies can result in systematic crisis that would lead to system failure. Economies that have a profitable banking sector are better able to withstand negative shocks and contribute to the stability of the financial system. This study analyses the determinants of banking profitability in Malaysia for 6 selected banks. The study use descriptive statistics and ordinary least squared method with normality, multiple regression, descriptive analysis unit root test and correlation